2015
DOI: 10.1186/s40200-016-0261-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of diabetes mellitus among children and adolescents in the district of Abidjan in Cote d’Ivoire: a population-based study

Abstract: BackgroundWorld Health Organization has predicted a worldwide rise in the prevalence of diabetes mellitus. Cote d’Ivoire is not exempted as evidenced by such factors as obesity and sedentary life style amongst others. The objective of the study was to determine the prevalence of diabetes mellitus (DM) among children and adolescents in the district of Abidjan in Cote d’Ivoire. MethodsA cross-sectional descriptive survey using a multi-stage sampling approach was conducted from March to April 2013. 1572 children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 16 publications
(22 reference statements)
3
8
0
Order By: Relevance
“…[ 3 , 12 , 26 ] Likely, the differences in study design and in the degree of urbanization contribute to the comparatively low proportion of IFG in the present analysis. [ 27 , 28 ] With regard to hypertension, the proportion of 9% was surprisingly high, compared to previous reports from urban Ghana (4%) [ 29 ], and given the percentile-based definition of hypertension (expected prevalence: 5%). While the available reference data stem from a large multi-ethnic survey [ 14 ], their application in sub-Saharan African settings is novel and may require independent verification.…”
Section: Discussionmentioning
confidence: 60%
“…[ 3 , 12 , 26 ] Likely, the differences in study design and in the degree of urbanization contribute to the comparatively low proportion of IFG in the present analysis. [ 27 , 28 ] With regard to hypertension, the proportion of 9% was surprisingly high, compared to previous reports from urban Ghana (4%) [ 29 ], and given the percentile-based definition of hypertension (expected prevalence: 5%). While the available reference data stem from a large multi-ethnic survey [ 14 ], their application in sub-Saharan African settings is novel and may require independent verification.…”
Section: Discussionmentioning
confidence: 60%
“…( 6 ) studied diabetes in clinical settings and found the prevalence of DM was 0·11 % in Chinese children. Several surveys conducted in other countries showed that the prevalence of DM was 0·4 % in Nigeria children and adolescents aged 2–19 years ( 20 ) , 0·3 % in American adolescents aged 10–19 years ( 21 ) and 0·45 % in the Saudi Arabian population aged 0–18 years ( 22 ) . Additionally, the present study observed Chinese children and adolescents had a lower IFG prevalence than their peers from Saudi Arabia ( 22 ) and America ( 23 ) (1·89 v .…”
Section: Discussionmentioning
confidence: 99%
“…In Africa, 39100 children aged 0-14 years have type 1A diabetes in 2013 [5]. In Côte d'Ivoire, 0.4% of children and adolescents are type 1 diabetics (T1D) [6]. It is an incurable disease that is gaining momentum in Africa and particularly in Côte d'Ivoire.…”
Section: Introductionmentioning
confidence: 99%